Comorbid SUNCT Syndrome and Opalski Syndrome Caused by Dorsolateral Medullary Infarction - Lei, Qi; Lv, Jianmeng; Kang, Bei; Guo, Hena; Fei, Yulang; Chen, Ruili; Guo, Hui; Yang, Qian (Frontiers in Neurology, 2020)
ABSTRACT Opalski syndrome is a rare variation of lateral medullary syndrome （LMS）accompanied by ipsilateral hemiparesis. Short-lasting unilateral neuralgiform headaches with conjunctival injection and tearing (SUNCT) is a rare headache syndrome which belongs to the trigeminal autonomic cephalalgias. SUNCT syndrome has been previously described in association with LMS. We here describe a case of SUNCT syndrome with Opalski syndrome caused by dorsolateral medullary infarction.